Analysis of ELSIMIL Service Utilization to Increase Knowledge on Stunting Prevention among Prospective Brides at the Tebing Tinggi Family Planning Extension Center - Helminawati Berutu; Harris Rambey; Raisha Octavariny; Karnirius Harefa; Elvi Era Liesmayani (JURNAL KESMAS DAN GIZI (JKG), 2026)
Poor nutritional status in prospective brides is one of the causes of stunting that needs to be identified early. Therefore, the ELSIMIL application was developed to detect stunting risk factors in prospective brides. This study aims to analyze the utilization of ELSIMIL services to increase knowledge about stunting prevention in prospective brides. This mixed-methods study employed a sequential mixed methods strategy, primarily an explanatory sequential strategy. The study population was 98, and accidental sampling resulted in a sample size of 32. Five informants participated in the study. Data validity was validated through triangulation. Quantitative data collection using questionnaires was analyzed using the chi-square test and logistic regression. Qualitative data collection using in-depth interviews was analyzed and discussed in narrative form. Results showed that of the eight variables, one variable (age) was not significantly related. Through logistic regression testing, the most dominant variable was information, with a p-value of 0.010 and Exp(B) of 28.095. Qualitative results showed that prospective brides and grooms who were introduced to the ELSIMIL app, provided with information on how to use the app, provided educational information within the app, and received ELSIMIL service support increased their knowledge and understanding of stunting prevention. In conclusion, utilizing ELSIMIL services can improve prospective brides and grooms' knowledge of stunting prevention. It is hoped that staff at the Family Planning Extension Center can expand their educational reach through youth social forums to make the delivery process more relaxed and easily understood by young prospective brides and grooms.